Pengaruh Harga Dan Promosi Terhadap Minat Beli Konsumen Melalui E-Commerce Shopee : Studi Pada Masyarakat Di Yogyakarta - Mu’jizah, Faridatul; Nuraini, Fitri; Nurjanah, Ekawati; Pramudita, Marlingga (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study is a descriptive study using SPSS version 2.2. to analyze the Effect of Price and Promotion on Consumers Buying Interest Through Shopee E-Commerce (Study on People in Yogyakarta). This study aims to analyze the effect of prices and promotions on consumers buying interest through Shopee E-Commerce. The data collection technique in this study used a questionnaire measured by a likert scale. In this study, there were 37 respondents in Yogyakarta who used Shopee E-Commerce in shopping. The analytical methods used in this study are instrument test, classical assumption test, multiple linear regression test, hypothesis test and determinant coefficient test. Based on the results of the study, it shows that: 1). Price has a positive effect on consumers buying interest through Shopee E-Commerce, 2). Promotions do not have a positive effect on consumers buying interest through Shopee E-Commerce. So, it can be concluded that price affects consumers buying interest through Shopee e-commerce, but promotions do not affect consumers buying interest through Shopee e-commerce.